Multisourcing in the technology sector in South Africa. - Bilgeri, Warren Gary. (My University, 2014)
ABSTRACT Globally, the practice of multisourcing is continuing to grow. Many companies are optimising the way research and development is staffed internally, outsourced, or carried out offshore. This research was undertaken to determine the factors that drive and influence multisourcing in South African technology companies. The literature was reviewed to determine the factors that drive and influence multisourcing at research and development companies globally. The South African information technology and electronics industries were reviewed to determine the extent of multisourcing in technology companies in South Africa. As literature on South African multisourcing is scarce, this research and the findings add more light on this subject. An in-depth, qualitative interview method was used to gather data on the factors that influence multisourcing. Senior executives from various information technology and electronics companies were interviewed on their company's multisourcing practices. The findings of this research are that most technology companies in South Africa operate within niche markets and view their research and development expertise as their core competency. These companies primarily employ skilled staff to carry out research and development functions. Many of these companies outsource some research and development locally. Larger companies that consist of geographically dispersed offices choreograph their research and development across their branches. Some companies prefer importing certain products developed overseas than developing these products in-house, if this makes business sense. Factors such as costs, risks, scalability and technology influence multisourcing decisions. These findings may be of value to companies wishing to optimise their multisourcing practices.
MBA 2013
Keywords: Contracting out , Electronic industries .